Cell membrane damage induced by phenolic acids on wine lactic acid bacteria - Campos, F.M. (2010)
The aim of this work was to investigate the effect of phenolic acids on cell membrane permeability of lactic acid bacteria from wine. Several phenolic acids were tested for their effects on the cell membrane of Oenococcus oeni and Lactobacillus hilgardii by measuring potassium and phosphate efflux, proton influx and by assessing culture viability employing a fluorescence technique based on membrane integrity. The experimental results indicate that hydroxycinnamic acids (p-coumaric, caffeic and ferulic acids) induce greater ion leakages and higher proton influx than hydroxybenzoic acids (p-hydroxibenzoic, protocatechuic, gallic, vanillic, and syringic acids). Among the hydroxycinnamic acids, p-coumaric acid showed the strongest effect. Moreover, the exposure of cells to phenolic acids caused a significant decrease in cell culture viability, as measured by the fluorescence assay, in both tested strains. The results agree with previous results obtained in growth experiments with the same strains. Generally, phenolic acids increased the cell membrane permeability in lactic acid bacteria from wine. The different effects of phenolic acids on membrane permeability could be related to differences in their structure and lipophilic character.